Diffusion of corporate sustainability in the ski industry. (6th May 2022) - McGrady, Pavlina; Golicic, Susan L.; Cottrell, Stuart P.
Business faces increasing environmental, social, economic, and institutional challenges and is uniquely positioned to greatly impact the continued development of sustainability. This paper examines the impact of external stakeholders and the internal organisation as predictors of corporate sustainability in the production of services. A corporate sustainability framework was tested using an online survey based on Diffusion of Innovation and prism of sustainability (PoS) theories with employees representing major Colorado ski resorts. Results show that internal firm innovativeness impacts corporate sustainability. While external stakeholder characteristics also influence corporate sustainability, the impact is much lower than and partially mediated by that of the firm. The framework, not previously applied in business services research, demonstrates the role of the institution as a sustainability dimension and positions the implementation of sustainability in the service industry as an innovation.